Pengaruh Promosi Media Sosial, Lokasi, dan Nilai Persepsian terhadap Kepuasan Konsumen pada Warteg Bunana - Threesya Erin; Muhammad Fadli Luran; Amirullah Amirullah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the importance of maintaining consumer satisfaction amidst increasingly fierce competition in the culinary business, where Warteg Bunana faces challenges in the form of a decline in the number of customers over the past two years. The objective of this research is to determine and analyze the influence of social media promotion, location, and perceived value on consumer satisfaction at Warteg Bunana in Batam City. The research method used is a quantitative approach with a survey method through the distribution of questionnaires to 100 respondents selected using simple random sampling techniques. Data were analyzed using multiple linear regression analysis via SPSS software. The findings indicate that simultaneously, social media promotion, location, and perceived value have a significant effect on consumer satisfaction with an F value of 21,940 and a significance value of 0.000 < 0.05. Partially, all three variables also have a significant influence on consumer satisfaction. The coefficient of determination (R Square) of 0.407 shows that these variables explain 40.7% of consumer satisfaction. The implications of this research suggest that Warteg Bunana management needs to increase social media promotion consistently and maintain location comfort and service quality to improve consumers' perceived value on a sustainable basis